Local and systemic metabolic adjustments to drought in maize: Hydraulic redistribution in a split‐root system. Issue 5 (19th September 2022) - Werner, Lena Maria; Hartwig, Roman Paul; Engel, Isabelle; Franzisky, Bastian Leander; Wienkoop, Stefanie; Brenner, Martin; Preiner, Julian; Repper, Dagmar; Hartung, Jens; Zörb, Christian; Wimmer, Monika Andrea
Abstract: Background: It is yet unknown how maize plants respond to a partial root drying under conditions of a limited total water supply, and which adaptation mechanisms are triggered under these conditions. Aims: The aims of this study were to assess whether partial root drying results in distinguishable local and systemic physiological and metabolic drought responses, and whether compensatory water uptake and/or alteration of root architecture occurs under these conditions. Methods: Maize plants were grown in a split‐root system. When plants were 20 days old, the treatments 'well‐watered', 'local drought' and 'full drought' were established for a period of 10 days. Shoot length and gas exchange were measured non‐destructively, root exudates were collected using a filter system and biomass, relative water content, osmolality and proline content were determined destructively at final harvest. Results: Local drought triggered stress responses such as reduced biomass, shoot length, relative water content and increased osmolality. Maintained root growth was systemically achieved by hydraulic redistribution rather than by altering root architecture. Local and systemic osmolyte adjustments contributed to this hydraulic redistribution. Conclusions: Both local and systemic metabolic responses helped the plants to induce hydraulic redistribution, enhance water availability and in consequence plant water relations. This resulted in a surprisingly well‐maintained root growth even in the drought stressed root compartment.